2015
DOI: 10.1002/ddr.21273
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of microRNAs in Cancer: Future Perspectives

Abstract: Preclinical Research The discovery of microRNAs (miRNAs) and their link with cancer has opened a new era in cancer therapeutics. Approximately, 18 - 24 nucleotides long, miRNAs can up-regulate or down-regulate gene expression in many cancer types and are respectively categorized as oncogenes (oncomirs) or tumor suppressors. Expression profiles of miRNAs with biomarker potential can be used for the classification, diagnosis, therapeutic treatment, and prognosis of different cancer types. miRNA mimics and miRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 97 publications
0
39
0
Order By: Relevance
“…MiRNAs have emerged as an important kind of diagnostic, prognostic and predictive biomarker for different types of cancer, and earned a promising role for cancer biology (10,11). In addition, miRNAs offer potential new avenues for cancer treatment, for instance by using miRNA mimics or antogomirs (12,13). …”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs have emerged as an important kind of diagnostic, prognostic and predictive biomarker for different types of cancer, and earned a promising role for cancer biology (10,11). In addition, miRNAs offer potential new avenues for cancer treatment, for instance by using miRNA mimics or antogomirs (12,13). …”
Section: Introductionmentioning
confidence: 99%
“…Due to this one-to-many relationship, studying miRNA expression profiles could contribute more efficiently to construction of the molecular regulatory network as a whole, especially in characterizing cancer-associated regulation of molecular pathways or biological processes. miRNAs can be classified as either tumor suppressors or oncogenes (oncomirs) according to their expression profiles in cancer [8]. In breast cancer, at least 20 oncogenic miRNAs or cluster families have been identified to promote cell proliferation, invasion, migration, or angiogenesis [9].…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have suggested that miRNAs perform a crucial role in regulating cancer cells by acting as oncogenes or tumor suppressers (9)(10)(11). Therefore, miRNAs may serve as potential biomarkers and targets for the diagnosis and treatment of various types of cancer (12).…”
Section: Introductionmentioning
confidence: 99%